Comparison of Pressurized Liquid Extraction and Matrix Solid Phase Dispersion for the Measurement of Semi-Volatile Organic Compound Accumulation in Tadpoles - Stanley, Kerri (2009)
Analytical methods capable of trace measurement of semi-volatile organic compounds (SOCs) are necessary to assess the exposure of tadpoles to contaminants as a result of long-range and regional atmospheric transport and deposition. The following study compares the results of two analytical methods, one using pressurized liquid extraction (PLE) and the other using matrix solid phase dispersion (MSPD), for the trace measurement of over 70 SOCs, including current-use pesticides, in tadpole tissue. The MSPD method resulted in improved SOC recoveries and precision compared to the PLE method. The MSPD method also required less time, consumed less solvent, and resulted in the measurement of a greater number of SOCs than the PLE method.